The Impact of sleep apnea on sleep quality - A literature review - Pelczar, Aleksandra; Oczkowska, Wiktoria; Morawska, Diana; Drabik , Przemysław Dominik; Malinowski, Alex; Marchewka, Klaudia; Sochocki, Radosław; Białek, Wiktoria; Sadowska, Agata; Bartosik, Kacper (Journal of Education, Health and Sport, 2026)
Background: Obstructive sleep apnea (OSA) is a common yet underdiagnosed disorder characterized by recurrent upper airway obstruction, leading to intermittent hypoxemia and micro-arousals. These disturbances fragment sleep and disrupt normal architecture. OSA affects not only respiration but also both subjective and objective sleep quality, contributing to daytime sleepiness, cognitive impairment, mood disturbances, and reduced quality of life. Aim: To evaluate the impact of OSA on sleep quality through a synthesis of clinical, observational, and interventional studies, with emphasis on subjective and objective measures, disease severity, and treatment effects. Materials and Methods: A narrative literature review was conducted using PubMed and Google Scholar. Included studies comprised observational, polysomnographic, interventional (CPAP), and systematic reviews. Findings were analyzed qualitatively. Results: Approximately two-thirds of OSA patients report poor, non-restorative sleep. Polysomnography shows increased arousals, reduced sleep continuity, and impaired slow-wave and REM sleep. Greater disease severity, particularly higher apnea–hypopnea index and hypoxemia, is associated with worse sleep quality and daytime dysfunction. Subjective measures often indicate greater impairment than objective findings. Poor sleep quality correlates with fatigue, cognitive deficits, mood disorders, and decreased productivity. CPAP improves sleep parameters and perceived sleep quality, though residual symptoms may persist due to comorbidities such as insomnia. Conclusions: Sleep quality impairment is a core feature of OSA. Sleep fragmentation and hypoxemia are key mechanisms driving non-restorative sleep. Discrepancies between subjective and objective measures highlight the need for patient-reported outcomes. While CPAP is effective, individualized, multimodal approaches are needed to fully restore sleep quality.